Mutation breeding of Cavendish bananas for resistance to Fusarium oxysporum f. sp. cubense tropical race 4 - Bothma, Sheryl (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.